1987
DOI: 10.1128/aac.31.3.452
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of 3'-azido-3'-deoxythymidine and 9-(1,3-dihydroxy-2-propoxymethyl)guanine for normal human hematopoietic progenitor cells in vitro

Abstract: The effects of 3'-azido-3'-deoxythymidine (AZT) and 9-(1,3-dihydroxy-2-propoxymethyl)guanine on myeloid and erythroid colony-forming cells were studied by clonogenic assays. Both consistently inhibited granulocytemacrophage CFU (CFU-GM) and erythroid burst-forming units in a dose-dependent fashion. Concentrations of AZT and 9-(1,3-dihydroxy-2-propoxymethyl)guanine required for 50% inhibition of CFU-GM were, respectively, 0.9 0.1 and 2.7 0.5 ,uM; those required for 90% inhibition were, respectively, 34.0 2.8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
96
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(103 citation statements)
references
References 10 publications
6
96
1
Order By: Relevance
“…1,6 The underlying mechanism of ganciclovir-related neutropenia is a dose-dependent inhibition of DNA-polymerase in hematopoietic progenitor cells. 7 We previously reported that ganciclovirrelated neutropenia is associated with low marrow cellularity, hyperbilirubinemia, and elevated serum creatinine levels after myeloablative conditioning (M-HCT). 1 However, it is not known how non-myeloablative conditioning (NM-HCT) influences the incidences of secondary cytopenias in general and ganciclovir-related neutropenia in particular.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 The underlying mechanism of ganciclovir-related neutropenia is a dose-dependent inhibition of DNA-polymerase in hematopoietic progenitor cells. 7 We previously reported that ganciclovirrelated neutropenia is associated with low marrow cellularity, hyperbilirubinemia, and elevated serum creatinine levels after myeloablative conditioning (M-HCT). 1 However, it is not known how non-myeloablative conditioning (NM-HCT) influences the incidences of secondary cytopenias in general and ganciclovir-related neutropenia in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Severe eosinophilia occurred in four (4.0%) patients at a median of 48.5 days (range 41-56) after CBT. The median duration was 2.5 days (range [1][2][3][4]. No study patients were treated for eosinophilia.…”
mentioning
confidence: 99%
“…The main reason for the association between pretransplant CMV seropositivity and less occurrence of moderate-to-severe eosinophilia after CBT is probably the myelotoxic effect of ganciclovir therapy against CMV infection. 3 The association between GVHD and eosinophilia within 100 days after CBT was studied. Grade II-IV acute GVHD occurred in 47 of 75 (62.7%) patients with mild-to-severe eosinophilia and 14 of 26 (53.8%) patients without mildto-severe eosinophilia (P ¼ 0.44 by Fisher's exact test).…”
mentioning
confidence: 99%
“…Especially from the nucleoside analogues, e.g. AZT, it is known that they toxically affect bone marrow progenitor cells (Sommadossi and Carlisle, 1987).…”
Section: Methodsmentioning
confidence: 99%